PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL MELALUI BUDGET EMPHASIS, KECUKUPAN ANGGARAN DAN PERSEPSI INOVASI SEBAGAI VARIABEL INTERVENING (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Kampar) - Enawan, Hanny; Hasan, Amir; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This reserch aims to examinethe effects of budget participation on managerial performance through budget emphasis, the adequacy of the budget and the perception of innovation as an intervening variablein SKPD Kampar Regency. This study uses primary data. Sample selection technique used is purposive sampling. Nine fields contained in twenty five SKPD that meet the sample criteria has been selected. The analytical method is multiple linear regression using SPSS version 17. The result shows thatbudget emphasis, the adequacy of the budget and the perception of innovation as an intervening variablehave a significant influence on budget participation on managerial performance.Keywords: budget emphasis, the adequacy of the budget, the perception of innovation and budget participation.